Using RAD-seq to identify and differentiate the medicinal herb Scrophularia ningpoensis and its adulterants - Lei Guo; Xia Wang; Hong Li; Mengli Zhou; Liqin Liu; Ruihong Wang; Pan Li (BMC Genomics)
Abstract Background Scrophulariae Radix, the dried root of Scrophularia ningpoensis Hemsl., belongs to the Scrophulariaceae family and is known for its diverse pharmacological effects, such as antihypertensive, anti-inflammatory, and antitumor properties. It is common that the Scrophulariae Radix is often contaminated by various adulterants like S. buergeriana, S. kakudensis, and S. yoshimurae in its medicinal usage. However, traditional methods for identifying Chinese medicinal materials have been found to be insufficient in accurately distinguishing S. ningpoensis from the three adulterant species. Results In this study, RAD-seq technology was employed to sequence 27 individuals from the four species, yielding 55,250 high-quality SNP sites. Genetic differentiation analysis using these sites revealed significant genetic divergence between S. ningpoensis and the three adulterants. Through assessment genetic structure, principal component, and phylogenetic analysis, these four species were effectively distinguished with a high degree of confidence. The phylogenetic results indicated that S. ningpoensis is more closely related to S. yoshimurae, while S. buergeriana shows a closer relationship with S. kakudensis, providing new reference information for understanding interspecific relationships among the four Scrophularia species. Conclusions This study successfully identified S. ningpoensis and the three adulterants, enriched the genomic information of Scrophularia species, and contributed to a more profound understanding of the evolutionary dynamics within this genus. Furthermore, it offers novel insights and methodologies for the identification of medicinal plants.